Elementary School Students' Perception Towards The Use of Gamification in Realistic Mathematic Education - Hayati, Rahmi; Nuraina (Genderang Asa: Journal of Primary Education, 2025)
This study aims to describe the perceptions of elementary school students towards the use of gamification in mathematics learning based on Realistic Mathematics Education (RME). In addition, this study also analyzes the factors that influence students' perceptions and explores the impact of gamification on students' motivation and understanding in learning mathematics. This study uses a qualitative approach with a case study method. Data were collected through interviews, observations, and open questionnaires involving elementary school students who had participated in gamification and RME-based mathematics learning. Data analysis techniques were carried out through data reduction, data presentation, and drawing conclusions with triangulation to ensure the validity of the findings. The results showed that students had a positive perception of the use of gamification in mathematics learning based on RME. Students feel more motivated, actively involved, and understand mathematical concepts better through this approach. In addition, it was found that gamification in RME increases students' learning motivation by making learning more interactive and fun. However, some students experience stress due to the competitive elements in gamification, so a balance is needed between challenges and exploration of mathematical concepts. Gamification in RME-based mathematics learning provides significant benefits in increasing students' motivation and understanding. However, its effectiveness depends on the right learning design, the role of teachers in facilitating positive interactions, and the balance between competition and concept exploration. The recommendation of this study is for teachers to develop gamification strategies that are appropriate to students' needs and characteristics and evaluate their long-term impact on mathematics learning outcomes.